A long-term follow-up of safety and clinical efficacy of NTCELL® [Immunoprotected (Alginate-encapsulated) porcine choroid plexus cells for xenotransplantation] in patients with Parkinson's disease. (January 2021) - Mulroy, Eoin; Snow, Barry; Bok, Arnold; Simpson, Mark; Smith, Andrew; Taylor, Kenneth M.; Lockhart, Michelle; Lam, B.B. Janice; Frampton, Christopher; Finucane, Gregory; Schweder, Patrick; Chen, Benson; et al.
Abstract: Introduction: In 2019, we published the results of a Phase IIb randomized controlled trial of putaminal encapsulated porcine choroid plexus cell (termed NTCELL®) administration in patients with Parkinson's disease. This study failed to meet its primary efficacy end-point of a change in UPDRS part III score in the 'off' state at 26-weeks post-implant. However, a number of secondary end-points reached statistical significance. We questioned whether with longer follow-up, clinically significant improvements would be observed. For this reason, we decided to follow-up all patients periodically to week 104. Herein, we report the results of this long-term follow-up. Methods: All 18 patients included in the original study were periodically re-assessed at weeks 52, 78 and 104 post-implant. At each time-point, motor and non-motor function, quality of life and levodopa equivalent daily dose was assessed using a standardized testing battery. Results: At week 104, no significant differences in UPDRS part III scores in the 'off' state were observed in any of the treatment groups compared to baseline. Only a single serious adverse event - hospitalisation due to Parkinson's disease rigidity not responding to changes in medications – was considered potentially related to the implant procedure. There was no evidence of xenogeneic viral transmission. Conclusion: Un-blinded, long-duration follow-up to week 104 post-implantation showed no evidence that putaminal NTCELL® administration produces significant clinical benefit in patients with moderately advanced Parkinson's disease. Highlights: At 104-weeks, striatal NTCELL® delivery failed to demonstrate clinical improvement. Striatal NTCELL® administration is safe and well tolerated. 120 NTCELL® per striatum is likely beyond the maximum tolerated dose.